1992
DOI: 10.1142/s0129083592000610
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Correlation of Trace Elements in Whole Blood With Acute Leukemia by Pixe

Abstract: The contents of multi-elements in whole blood from 115 patients with 7 different types of acute leukemia and 38 well matched healthy controls have been determined by means of proton induced X-ray emission (PIXE). The number of available analyzed elements was as many as 11, mainly due to the use of a 100 um thick Cr funny foi1 as an absorber. The contents of elements Cu, Ca, S, P, Si and the ratio of Cu to Zn (Cu/Zn) were higher and those of elements Zn, K, Fe, Al and Rb were lower with high significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A1, Si, P, S, K, Ca, Mn, Fe, Cu, Zn and Rb. A fairly good result of the correlation of trace elements in whole blood with acute leukemia was obtained [4,5]. The results showed that the 0168-583X/96/$15.00 Copyright © 1996 Elsevier Science B.V. All rights reserved SSDI 0168-583X(95 )00889-6 II.…”
Section: Pixe Analysis Of Blood Samplesmentioning
confidence: 98%
“…A1, Si, P, S, K, Ca, Mn, Fe, Cu, Zn and Rb. A fairly good result of the correlation of trace elements in whole blood with acute leukemia was obtained [4,5]. The results showed that the 0168-583X/96/$15.00 Copyright © 1996 Elsevier Science B.V. All rights reserved SSDI 0168-583X(95 )00889-6 II.…”
Section: Pixe Analysis Of Blood Samplesmentioning
confidence: 98%